Pengaruh Self-Regulated Learning, Dukungan Teman Sebaya, dan Kualitas Pembelajaran terhadap Hasil Belajar Siswa Jurusan Bisnis Digital Melalui Motivasi Belajar pada Mata Pelajaran Dasar - Dasar Program Kejuruan: Studi di SMKS Budi Agung Medan Tahun Ajaran 2025/2026 - Linsa Febby Br Barus; Pasca Dwi Putra (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Learning outcomes in vocational education are influenced by multiple internal and external factors, including self-regulated learning, peer support, learning quality, and students' learning motivation. Understanding the interaction among these variables is essential for improving learning effectiveness, particularly in Digital Business vocational programs. This quantitative study employed an explanatory survey design involving 60 students of the Digital Business Department at SMKS Budi Agung Medan during the 2025/2026 academic year. The entire population was selected using a saturated sampling technique. Data were collected through Likert-scale questionnaires and documentation of students' achievement scores, then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Instrument quality was evaluated through convergent validity, discriminant validity, composite reliability, and Cronbach's alpha before structural model assessment. The findings indicate that learning quality has a positive and significant effect on learning motivation, whereas self-regulated learning and peer support do not significantly influence learning motivation. Self-regulated learning, peer support, learning quality, and learning motivation also do not have significant direct effects on learning outcomes. Furthermore, learning motivation fails to mediate the relationship between the independent variables and learning outcomes. These findings emphasize that improving instructional quality plays a more substantial role in fostering students' motivation than directly improving academic achievement. The study contributes empirical evidence regarding the structural relationships among learning-related variables in vocational education and provides recommendations for strengthening instructional practices to enhance student learning experiences.